Critical ductile fracture criterion based on first principal stress and stress triaxiality. (October 2020) - Yu, Simiao; Cai, Lixun; Yao, Di; Bao, Chen
Highlights: Obtain the full-range equivalent stress-strain relations of ductile materials by using finite-element-analysis aided testing method, and simulate the fracture tests of ten types of specimens accurately. Investigate the critical fracture failure behaviours of ductile materials in detail, and confirm the important influence of the first principal stress on the ductile fracture failure. Propose a novel dual-parameter critical fracture criterion represented by the critical first principal stress and critical stress triaxiality, and prove the validity of the proposed criterion. Abstract: A series of quasi-static fracture tests on ten types of specimens for six types of materials were performed to investigate the ductile fracture failure behavior of materials. The full-range equivalent stress-strain relations of materials were obtained by using finite-element-analysis aided testing method. The critical failure behavior was discussed in detail by the analysis of the local stress and strain distributions on the cross-sections of specimens and fractographic observation of specimens. The results show that the first principal stress is the dominant factor of ductile fracture failure. A novel critical fracture criterion of ductile materials represented by the critical first principal stress and critical stress triaxiality is proposed, and the validity of the proposed criterion has been successfully examined.